2011
DOI: 10.1302/0301-620x.93b8.26560
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled trial of circumpatellar electrocautery in total knee replacement without patellar resurfacing

Abstract: The efficacy of circumpatellar electrocautery in reducing the incidence of post-operative anterior knee pain is unknown. We conducted a single-centre, outcome-assessor and patient-blinded, parallel-group, randomised, controlled trial to compare circumpatellar electrocautery with no electrocautery in total knee replacement in the absence of patellar resurfacing. Patients requiring knee replacement for primary osteoarthritis were randomly assigned circumpatellar electrocautery (intervention group) or no electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(106 citation statements)
references
References 35 publications
(52 reference statements)
3
89
2
Order By: Relevance
“…33 These pain receptors are destroyed by electrocautery, to reduce postoperative AKP. An observational study comparing two groups of patients (n = 131 each) undergoing patellar nonresurfacing in TKA, with or without circumpatellar electrocautery, 34 found that the incidence of AKP was significantly lower in the group receiving circumpatellar electrocautery than in the other group. In two prospective studies, circumpatellar electrocautery was performed in both patellar resurfacing and patellar nonresurfacing TKA.…”
Section: Discussionmentioning
confidence: 99%
“…33 These pain receptors are destroyed by electrocautery, to reduce postoperative AKP. An observational study comparing two groups of patients (n = 131 each) undergoing patellar nonresurfacing in TKA, with or without circumpatellar electrocautery, 34 found that the incidence of AKP was significantly lower in the group receiving circumpatellar electrocautery than in the other group. In two prospective studies, circumpatellar electrocautery was performed in both patellar resurfacing and patellar nonresurfacing TKA.…”
Section: Discussionmentioning
confidence: 99%
“…The synovium, lateral retinaculum, infrapatellar fat pad, periosteum and subchondral bone of patellae affected with degenerative disease are all richly supplied with type Ⅳa FNEs and fibres containing Substance P [2] . A key aim of this study was to identify literature evaluating the different determinants of AKP after a TKA was found [2,8,9,12,13,15,18,22,23,[25][26][27]30,34,[36][37][38][39][40][41] . The articles reviewed confirm this study's hypothesis that anything that alters the patellofemoral joint (PFJ) mechanics can activate these FNEs and thus induce AKP after TKA [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation of this study is that the main focus should be on determining the correct placement and maybe incorporating the ACL (if present) in TKA placement. [23] . One study found a lower prevalence of AKP due to the resection of Hoffa's fat pad [66] .…”
Section: A B D Cmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In our study, post-surgical knee flexion was significantly lower in patients submitted to PD (p = 0.009), which is not consistent with function results previously described. Considering that a reduction in knee range of motion can occur in patients TKA in general, 14 more research is needed to better assess this variable.…”
Section: ■ Discussionmentioning
confidence: 99%